Comparison of Two Methods for Assaying Reducing Sugars in the Determination of Carbohydrase Activities - Alexander V. Gusakov; Elena G. Kondratyeva; Arkady P. Sinitsyn (International Journal of Analytical Chemistry)
The Nelson-Somogyi (NS) and 3,5-dinitrosalicylic acid (DNS) assays for reducing sugars are widely used in measurements of carbohydrase activities against different polysaccharides. Using twelve commercial enzyme preparations, the comparison of the NS and DNS assays in determination of cellulase, β-glucanase, xylanase, and β-mannanase activities was carried out. When cellulase activities against CMC were measured, the DNS assay gave activity values, which were typically 40–50% higher than those obtained with the NS assay. In the analysis of the xylanase, β-mannanase, and β-glucanase activities, the overestimations by the DNS assay were much more pronounced (the observed differences in the activities were 3- to 13-fold). Reasons for preferential use of the NS assay for measuring activities of carbohydrases other than cellulases are discussed.